2013
DOI: 10.1519/jsc.0b013e31825fce65
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Standing Long Jump From Varying Starting Positions

Abstract: The purpose of this study was (a) to investigate the effect of the different foot movement (placement) during take-off and the initial knee joint angle used in standing long jump by the ground reaction forces analysis and 3-dimensional motion analysis (BTS SMART motion) and (b) investigate how the jump performances of different foot placement is related to the electromyography (EMG) activity (Noraxon) of 3 selected muscle groups (m. gastrocnemius, m. gluteus maximus, m. rectus femoris, m. tibialis anterior, m.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
0
27
0
1
Order By: Relevance
“…An application of vertical and horizontal types of jumping exercises could contribute to longer SL ( Coh and Mackala, 2013 ; Kotzamanidis, 2003 ; Mackala et al, 2012 ). However, a strong relationship between these variables has not been established in athletes ( Farrar and Thorland, 1987 ), which is consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
“…An application of vertical and horizontal types of jumping exercises could contribute to longer SL ( Coh and Mackala, 2013 ; Kotzamanidis, 2003 ; Mackala et al, 2012 ). However, a strong relationship between these variables has not been established in athletes ( Farrar and Thorland, 1987 ), which is consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
“…The applied training program comprised dynamic exercises with higher loads (because of the preparatory training period of the volleyball players) which significantly shorten the ground contact time of the foot and improve jumping quality. During swinging movements, as Maćkała (Mackala, Stodolka, Siemienski, Coh, 2013) claim, the most active are the rectus femoris muscle and the tibialis anterior muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However, the significant finding of our study on the hip ROM during take-off had been agreed by previous studies. During the jumping movement, the selection of the take-off angle of the lower trunk flexion on hip angle besides lower knee angle promotes the jumping performance (Fernandez-Santos et al, 2018;Mackala, Stodółka, Siemienski, & Ćoh, 2013) analysis on the developmental jumping movement with the age-factor determinant among typically developing children with key variable of take-off angle (Fernandez-Santos et al, 2018) had found that it was significantly correlated in the movement evaluation of horizontal distance (r = .276; p <.01). Otherwise, the current study finding of hip-knee plots may not give strong impression the significant hip angle of take-off phase across the groups.…”
Section: Discussionmentioning
confidence: 99%